Electronic sales on an international level - The provisions within the framework of the Rome I Regulation - Pipilou, Aikaterini (Technium Social Sciences Journal, 2025)
The key and fundamental characteristics of electronic sales on an international level include the remote conclusion of electronic sales contracts, the use of electronic means, the existence of General Terms and Conditions (GTC) of electronic sales contracts, as well as the accession to contracts. The issues arising from these characteristics are addressed by legal science. Electronic sales at the international level are mainly regulated by the Rome I Regulation, which explicitly ensures the unobstructed realization of electronic commerce concerning contracts between consumers as well as between consumers and professionals. The lack of provisions for procedural issues related to electronic sales within the framework of Regulation Rome I is a significant concern, while the coexistence of Regulation Rome I with legislative texts for consumer protection is crucial. Finally, of major importance are the issues surrounding mandatory law rules as directly applicable within the framework of Regulation Rome I, as well as the balancing role of Regulation Rome I between consumer protection and the facilitation of electronic sales contracts.